2008
DOI: 10.1074/jbc.m707328200
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Deprivation Stimulates O-GlcNAc Modification of Proteins through Up-regulation of O-Linked N-Acetylglucosaminyltransferase

Abstract: O-Linked N-acetylglucosamine (O-GlcNAc (1-4). In the cell, the HBP converts imported glucose and glucosamine to UDP-GlcNAc. Glutamine:fructose-6-phosphate amidotransferase is the rate-limiting enzyme in this pathway. OGT catalyzes GlcNAc transfer to serine and threonine residues of target proteins, whereas O-O-GlcNAc is known to affect multiple metabolic pathways and has been implicated specifically as a contributor to insulin resistance and type 2 diabetes (5-7). Chronically elevated HBP flux, a result of hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
140
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(166 citation statements)
references
References 38 publications
20
140
4
Order By: Relevance
“…Fig. 1A it can be seen that removal of glucose from NRVMs resulted in a time-dependent increase in O-GlcNAc levels; this increase was apparent, particularly in high molecular mass proteins, within 3 h of glucose deprivation, and overall O-GlcNAc levels were significantly increased by 6 h and reached maximal levels by 12 h. In contrast to studies in other cell lines we did not observe an initial decrease in O-GlcNAc levels in response to glucose deprivation (25,27). Glucose is a primary energy source for cardiomyocytes; therefore, glucose deprivation was repeated for 6 h with and without 1 mM and 10 mM pyruvate, which is readily oxidized by cardiomyocytes for energy production.…”
Section: Methodscontrasting
confidence: 51%
See 3 more Smart Citations
“…Fig. 1A it can be seen that removal of glucose from NRVMs resulted in a time-dependent increase in O-GlcNAc levels; this increase was apparent, particularly in high molecular mass proteins, within 3 h of glucose deprivation, and overall O-GlcNAc levels were significantly increased by 6 h and reached maximal levels by 12 h. In contrast to studies in other cell lines we did not observe an initial decrease in O-GlcNAc levels in response to glucose deprivation (25,27). Glucose is a primary energy source for cardiomyocytes; therefore, glucose deprivation was repeated for 6 h with and without 1 mM and 10 mM pyruvate, which is readily oxidized by cardiomyocytes for energy production.…”
Section: Methodscontrasting
confidence: 51%
“…2A). This contrasts with other reports that glucose deprivation resulted in increased levels of OGT protein and decreased OGA protein (25,27). To determine whether the changes in OGA and OGT protein levels were due to altered transcription, we determined the effects of glucose deprivation on OGA and OGT mRNA levels and found that transcript levels for both were increased following removal of glucose (Fig.…”
Section: Glucose Deprivation Increases O-glcnac Levels In a Timeand Dcontrasting
confidence: 54%
See 2 more Smart Citations
“…Inhibitors of bacterial protein synthesis cause an increase in the concentrations of peptidoglycan precursors, including UDP-GlcNAc [3]. These physiological changes in UDP-GlcNAc pools have created a need for rapid assays to analyze the large number of samples produced during time course experiments [4].…”
Section: Introductionmentioning
confidence: 99%